2011
DOI: 10.1002/sia.3731
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical impedance spectroscopy and in situ UV‐vis spectroelectrochemistry studies of Poly(N‐vinyl carbazole)/ Polydimethylsiloxane composite electrodes

Abstract: Poly(N-vinyl carbazole)/polydimethylsiloxane (PNVCz/PDMS) composite electrodes were prepared by electrochemical polymerization of NVCz monomer onto PDMS-coated platinum (Pt) and glassy carbon (GC) electrode surfaces to investigate the influence of the insulating constituent, PDMS and process temperature on the capacitive performance of the coated layers. The electrochemical properties of the bilayer coatings were studied by electrochemical impedance spectroscopy and UV-vis spectroelectrochemistry measurements.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In our previous studies, we prepared both copolymers of NVCz with AA (acrylic acid), IA (itaconic acid) and NIPAAm ( N ‐isopropylacrylamide) by free‐radical solution polymerization using AIBN as initiator, and PNVCz/polydimethylsiloxane (PDMS) composite electrodes by electrochemical polymerization of NVCz monomer onto PDMS‐coated platinum (Pt) and glassy carbon (GC) electrode surfaces . In our another paper, we investigated the effect of intercalation agent and mixing method on the morphologic, thermal and electrochemical properties of PNVCz‐based composite materials prepared by in situ free radical polymerization in the presence of CAN and two‐dimensional MMT layers as initiator and inorganic component, respectively, and observed that the improvement intermolecular interactions, the widened interlayer distances and more homogeneous morphologies were obtained with PNVCz/ODA (octadecyl amine)—MMT composites, when ODA as intercalating agent and sonication with high‐power sonic tip as mixing method were used for modification and dispersion of silicate layers, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we prepared both copolymers of NVCz with AA (acrylic acid), IA (itaconic acid) and NIPAAm ( N ‐isopropylacrylamide) by free‐radical solution polymerization using AIBN as initiator, and PNVCz/polydimethylsiloxane (PDMS) composite electrodes by electrochemical polymerization of NVCz monomer onto PDMS‐coated platinum (Pt) and glassy carbon (GC) electrode surfaces . In our another paper, we investigated the effect of intercalation agent and mixing method on the morphologic, thermal and electrochemical properties of PNVCz‐based composite materials prepared by in situ free radical polymerization in the presence of CAN and two‐dimensional MMT layers as initiator and inorganic component, respectively, and observed that the improvement intermolecular interactions, the widened interlayer distances and more homogeneous morphologies were obtained with PNVCz/ODA (octadecyl amine)—MMT composites, when ODA as intercalating agent and sonication with high‐power sonic tip as mixing method were used for modification and dispersion of silicate layers, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main methods used for their preparation is based on a condensation reaction of the reticulating agents with terminal silanol groups in the chain of polydimethylsiloxane (PDMS). [9][10][11][12] There are literature reports 13,14 on the use of PDMS in electrodes as the substrate base for chips or sensors and as coatings for solid electrode surfaces. Nevertheless, there are no reports of PDMS used as bulk component of an electrode material.…”
Section: Introductionmentioning
confidence: 99%